Faktorer som påverkar stereotypier hos häst - Orosco Lindström, Vendela (2019)
The horse is an herbivore herding animal, living in small family groups and spend most of the day searching for food. Modern horse-keeping can limit the possibilities for the horse to perform its natural behaviors, that can lead to a stereotypic behavior. With an increasing population of horse-owners, there is too little knowledge on management of horses. The aim of this study was to increase the understanding of how the stereotypic behavior originates and consequently how the horse-owner can adjust routines to affect the frequency to act in a preventive way. The study had two research issues: Which factors affect the young horse to commence a stereotype? How can horse-owners adapt the surrounding environment for a horse with a stereotypic behavior?